CREATIVE INDUSTRY IN TERMS OF COVID-2019 PANDEMIC: EUROPEAN COUNTRIES RESPONSIVE MEASURES. (2021) - Bhowmik, Roni; Debnath, Gouranga Chandra; Zafar, Raja Fawad; Lormon, Bruce Lortile
No abstract available